Collective behavior in an early Cambrian arthropod. - Hou, X; Siveter, D; Aldridge, R; Siveter, D (2008)
Examples that indicate collective behavior in the fossil record are rare. A group association of specimens that belong to a previously unknown arthropod from the Chengjiang Lagerstätte, China, provides evidence that such behavior was present in the early Cambrian (about 525 million years ago), coincident with the earliest extensive diversification of the Metazoa, the so-called Cambrian explosion event. The chainlike form of these specimens is unique for any arthropod, fossil or living, and most likely represents behavior associated with migration.